Enhancing motivation through music videos with lyrics, downloaded from You Tube for the reading comprehension process of eighth graders at Estados Unidos de América, Junior High School - Miranda Cáceres, Kathia Marisol; Vega Loo, Javier Antonio; Candanedo, Wilmo (David, Panamá : UDELAS, 2013)
The development of this research is focused on diagnosis of causes and effects of the development of classroom motivation in learning english in Junior High School students, whose main contribution is to stimulate interest in teaching a second language through music video as a technique for the reading comprehension process in an enjoyable and funny environment, thus, to avoid monotonous classes and lack of interest by the students.
TABLE OF CONTENTS INDEX TABLE INDEX GRAPHIC INTRODUCTION CHAPTER I: ANTECEDENTS AND STATEMENT OF THE PROBLEM CHAPTER II: THEORETICAL FRAMEWORK 2.1. Enhancing motivation through You Tube music videos 2.1.1. Description of krashen's (1981) Theory of second language adquisition 2.1.2. The acquisition-learning 2.1.3. The monitor hypothesis 2.1.4. The natural order hypothesis 2.1.5. The input hypothesis 2.1.6. The affective filter 2.2. The influence of music on neurons 2.3. The effects of music on the brain: The power of rhythm 2.4. The connection between music, reading and language development 2.4.1. The relationship betwwen music and reading in beginning readers 2.5. Reading comprehension 2.5.1. Reading comprehension development 2.5.2. Importance of reading comprehension 2.5.3. Vocabulary development increase reading comprehension 2.5.4. The effect of music on reading comprehension 2.6. Effects that music videos have in motivating students to improve their reading comprehension 2.7. The audio visual method CHAPTER III: METHODOLOGICAL FRAMEWORK CHAPTER IV: ANALYSIS OF RESULTS CONCLUSION RECOMMENDATIONS BIBLIOGRAPHY ANNEX
Incluye Table of content
Documento presentado para optar por el título de Licenciatura en Docencia en Inglés
Incluye Bibliografía
No se presta a domicilio
No se saca fotocopia
Keywords: ENGLISH -- TESIS DE LICENCIATURA -- READING; FACULTAD DE EDUCACIÓN SOCIAL Y ESPECIAL; ESCUELA DE EDUCACIÓN SOCIAL; LICENCIATURA EN DOCENCIA EN INGLÉS; ESTADOS UNIDOS DE AMÉRICA, JUNIOR HIGHT SCHOOL